Conditions of Workers Who Worked from Home during the Covid-19 Pandemic in Indonesia - Prastiwi, Lustina Fajar; Arisetyawan, Kukuh; Wahyuningsih, Rani Destia; Abidin, Farid (KnE Social Sciences, 2024)
Work from Home (WFH) is one of the policies implemented by the Indonesian government to contain the cases of Covid-19 in Indonesia since March 2020. People were required to adapt to the new normal way of working by means of WFH. WFH applied to workers in both formal and informal sectors. While those working in the formal sector can get a lot done through remote working, the types of work that can be done remotely in the informal sector are still very limited. The WFH way of working has finally become a trend that is considered flexible and has advantages for the workforce to be more productive without having to leave the house. By using the logit model, this study seeks to answer the characteristics of the formal and informal sector workers who work at home as an effect of the Covid-19 pandemic. The result show that the Covid-19 pandemic was the primary reason why workers did WFH and that a majority of them are from the formal sector. The activities of the majority of the workforce during WFH are communication, promotion, and transactions which are mostly carried out by married women workers. In addition, workers who do WFH tend to be young workers who are highly educated and are familiar with the internet. Keywords: labor characteristics, work from home, Indonesia